2022
DOI: 10.1021/acs.langmuir.2c00570
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Interactions in the Graphene-Directed Assembly of Monolayer Conjugated Polymers

Abstract: Development of graphene−organic hybrid electronics is one of the most promising directions for next-generation electronic materials. However, it remains challenging to understand the graphene− organic semiconductor interactions right at the interface, which is key to designing hybrid electronics. Herein, we study the influence of graphene on the multiscale morphology of solution-processed monolayers of conjugated polymers (PII-2T, DPP-BTz, DPP2T-TT, and DPP-T-TMS). The strong interaction between graphene and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…23 Another prototypical conjugated polymer poly(bisdodecylquaterthiophene) (PQT) shows highest electrical conductivity of 350 S/cm after introducing sulphur atoms into the side chains and doped with NOBF 4 . 24 The alteration of energy levels due to chemical structure modification facilitates integer charge transfer between the polymer and the dopants 21,25 , where the microstructure of the doped polymer film plays a dominant role in controlling electrical conductivity. The modification of sidechains with certain atoms promotes the interaction between the side chains and dopant molecules, thus increasing the lamellar distance while closely packing the polymer backbone, which promotes the charge transport along the - stacking direction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Another prototypical conjugated polymer poly(bisdodecylquaterthiophene) (PQT) shows highest electrical conductivity of 350 S/cm after introducing sulphur atoms into the side chains and doped with NOBF 4 . 24 The alteration of energy levels due to chemical structure modification facilitates integer charge transfer between the polymer and the dopants 21,25 , where the microstructure of the doped polymer film plays a dominant role in controlling electrical conductivity. The modification of sidechains with certain atoms promotes the interaction between the side chains and dopant molecules, thus increasing the lamellar distance while closely packing the polymer backbone, which promotes the charge transport along the - stacking direction.…”
Section: Introductionmentioning
confidence: 99%
“…12–15 Among various conjugated polymer families, polythiophene derivatives show the most promising optical and electrical characteristics where the electrical conductivity is significantly improved through structural modifications, doping strategies, and by controlling the microstructure through process optimization. 16–21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies showed that the oxide or chemically modified graphene with different functional groups could be dispersed in polar or nonpolar solvents. However, a significant disadvantage of this method is the destruction of π-orbitals in graphene and the deterioration of its electrical conductivity and mechanical properties. , Instead of using environmentally hazardous organic solvents and surfactants, it seems reasonable to use biodegradable polymers as stabilizers in aqueous media to achieve better stability and higher nanosheet concentrations. , Using this method, the obtained colloidal solution provides an ideal starting material for graphene-based nanocomposite preparation. In particular, the colloidal solution obtained has a high graphene/polymer ratio that can be used in 3d printing, membranes, and other electrical devices. ,, …”
Section: Introductionmentioning
confidence: 99%
“…23−25 In particular, the colloidal solution obtained has a high graphene/polymer ratio that can be used in 3d printing, membranes, 26 and other electrical devices. 24,27,28 The polymer assisting exfoliation mechanism is often correlated to the steric forces formed between polymer chains adsorbed physically or chemically on atomic surfaces. 29 Polymer-covered nanosheets induce a repulsive force between each other, which prevents further agglomeration.…”
Section: Introductionmentioning
confidence: 99%